Sleep bruxism in children: relationship with screen-time and sugar consumption - Restrepo, Claudia; Santamaría, Adriana; Manrique, Rubén (Sleep medicine. X, 2021)
Consumption of added sugar and excessive screen-time is increasing worldwide and is associated with sleeping and behavior disorders, which are related with possible Sleep Bruxism (SB) in children. Therefore, the objective of this investigation was to examine the relationship between screen-time and sugar-consumption and possible SB in children. A cross-sectional study, including parents of 460 4- to 8-year-old children, was performed. Frequency of possible SB was assessed with the Children's Sleep Habits Questionnaire; sugar consumption with the Health Behaviour in School-Aged Children Food-Frequency Questionnaire. Comprehensive measures of screen-time (including cell phones, computers, electronic devices, electronic games, and TV) were taken. The time was recorded in hour/day. All data were analyzed with STATA© data analysis and statistical software version 13.0 (Copyright 1996–2016; Stata-Corp LP, College Station, TX, USA). Spearman correlation test and ordinal-multiple-variable regression analyses were used. Data of 440 subjects Mean age 6.2 years (S.D. 1.8) were analyzed. Prevalence of possible SB was 35% and screen-time was available for 92.9% of the children. Mean screen-time was 2.1 h/day. Parents reported 73% of the children (n = 319) to consume added sugar once a day every day and 20% more than once every day. Correlations of possible SB were statistically significant with screen-time (Rho = 0.8; p = 0.002) and sugar-consumption (Rho = 0.7; p = 0.03). Associations were found between possible SB and increase-to-increase screen-time and sugar-consumption (OR > 2). The results of this study demonstrated that as screen-time and sugar consumption increased, the frequency of bruxism in children increased. •Sleep bruxism is regulated centrally and deals with the reward system, particularly the neurotransmission of dopamine.•Sugar and the excessive use of screens alter neurotransmission of dopamine.•Excessive sugar consumption and increased screen time are common behaviors in children.•Parenting habits affects the consumption of sugar, the use of screens and the occurrence of sleep bruxism.